Membrane Modulates Affinity for Calcium Ion to Create an Apparent Cooperative Binding Response by Annexin a5 - Gauer, Jacob W. (The Biophysical Society, 2013)
Isothermal titration calorimetry was used to characterize the binding of calcium ion (Ca(2+)) and phospholipid to the peripheral membrane-binding protein annexin a5. The phospholipid was a binary mixture of a neutral and an acidic phospholipid, specifically phosphatidylcholine and phosphatidylserine in the form of large unilamellar vesicles. To stringently define the mode of binding, a global fit of data collected in the presence and absence of membrane concentrations exceeding protein saturation was performed. A partition function defined the contribution of all heat-evolving or heat-absorbing binding states. We find that annexin a5 binds Ca(2+) in solution according to a simple independent-site model (solution-state affinity). In the presence of phosphatidylserine-containing liposomes, binding of Ca(2+) differentiates into two classes of sites, both of which have higher affinity compared with the solution-state affinity. As in the solution-state scenario, the sites within each class were described with an independent-site model. Transitioning from a solution state with lower Ca(2+) affinity to a membrane-associated, higher Ca(2+) affinity state, results in cooperative binding. We discuss how weak membrane association of annexin a5 prior to Ca(2+) influx is the basis for the cooperative response of annexin a5 toward Ca(2+), and the role of membrane organization in this response.